Integration of Medical and Biological Physics With General Physics: Advancements and Applications in Healthcare and Technology - Salih, Abeer Ali; Jasim, Reem Basim; Fahd, Thu-Alfaqaar Kareem Eunuz; Shami, Haider Mazhar; Ali, Haya Qaied (American Journal of Botany and Bioengineering, 2025)
The integration of medical and biological physics with general physics has led to significant advancements in healthcare and technology, yet a comprehensive framework bridging these disciplines remains underdeveloped. This study explores the intersection of physics, biophysics, and medical applications, highlighting the role of fundamental physical principles in understanding biological systems and improving medical technologies. Through an interdisciplinary review, we analyze the contributions of physics to medical imaging, radiation therapy, biomechanics, nanotechnology, and bioinformatics. Findings reveal that leveraging physics-based methodologies enhances diagnostic precision, treatment efficacy, and the development of innovative medical devices. The results underscore the necessity of interdisciplinary collaboration to address emerging challenges in healthcare. This research provides a foundation for future technological innovations and fosters a deeper integration of physics into biomedical sciences.